Is there a Role for Gallium-67 Citrate SPECT/CT, in Patients with Renal Impairment or Who are Renal Transplant Recipients, in Identifying and Localizing Suspected Infection? - Nowosinska, Ewa; Navalkissoor, Shaunak; Quigley, Ann; Buscombe, John (World Journal of Nuclear Medicine, 2015)
To assess the added value of single-photon emission computed tomography/computed tomography (SPECT/CT) in patients with end-stage renal failure (ESRF) or renal transplant recipients in whom focal infection was suspected. Gallium-67 (Ga-67) citrate scintigrams of 18 patients (10 in ESRF and eight with renal transplants) were reviewed. Sites of abnormal uptake seen on the whole body and SPECT were noted. A SPECT/CT was also reviewed to see if additional information could be obtained. Imaging results were compared with the final diagnosis. Overall, 14 out of 18 (78%) patients had a proven cause to explain symptoms while four patients did not have a final cause identified. Infection was proven in the final diagnosis in 12 out of 14 (86%) patients. Of the 10 patients with ESRF, six had confirmed infection with the Ga-67 citrate study correctly identifying five out of six (83%) patients, and SPECT/CT providing additional information in four out of five (80%) patients. In the eight renal transplant recipients, six had a confirmed source of infection (all identified by the Ga-67 citrate study). SPECT/CT provided additional information in two out of six (33%) patients. Ga-67 citrate imaging had an overall sensitivity of 13/14 (93%), with one false negative. SPECT/CT provided an additional contribution in eight out of 18 (44%) patients by better defining the location/extent of infection and differentiating the physiological from the pathological uptake.
Keywords: Gallium-67 citrate; infection; renal failure; single-photon emission computed tomography/computed tomography